Analysis of Students’ Creative Thinking Skills in Solving Scatter Plot Problems in Terms of Self-Efficacy - Dinda Anggraeni; Agus Prasetyo Kurniawan; Luluk Mahmuda (Jurnal Inovasi Pendidikan Matematika (JIPM), 2026)
The ability of students to think creatively in solving mathematical problems, especially scatterplot problems, is significantly influenced by various factors, one of which is self-efficacy or students' belief in their abilities. Students with high levels of self-efficacy are usually more capable of overcoming challenges in learning, while students with low self-efficacy often feel hindered and less motivated to find creative solutions. This study aims to investigate the impact of self-efficacy on students' creative thinking abilities in solving scatterplot problems. The study involved students from varying levels of self-efficacy, categorized into three groups: high, moderate, and low. Data were collected through a questionnaire to measure self-efficacy, a creative thinking test, and in-depth interviews to gain insights into students' approaches to solving problems. The results of the study showed that students with high self-efficacy tended to be more creative, confident, and flexible in solving problems, while students with low self-efficacy experienced difficulties in creative thinking, felt uncertain, and avoided challenges. This study highlights the importance of developing self-efficacy in mathematics education, especially in enhancing students' creative thinking abilities. Therefore, teaching strategies that support the improvement of students' self-efficacy can strengthen their creativity and performance in solving more complex problems.